THE THE SYMBOLIC MEANING OF WEDANG UBLEK TRADITION IN THE HAUL OF MBAH ABDUSSHOMAD JOMBOR IN CIPETE VILLAGE, CILONGOK DISTRICT, BANYUMAS REGENCY: A PAUL RICOEUR'S HERMENEUTIC PERSPECTIVE - Ida Novianti; Farah Syiva Sani (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2026)
This study examines the Wedang ublek tradition practiced during the Haul (annual commemoration) of Mbah Abdusshomad Jombor in Cipete Village, Cilongok District, Banyumas Regency, Central Java, Indonesia. This research aims to describe the procession of the Wedang ublek tradition and analyze its symbolic meanings using Paul Ricoeur's hermeneutic interpretation theory. This qualitative research employs a cultural studies approach with field research methodology. Data were collected through literature study, in-depth interviews with traditional practitioners, descendants (dzurriyah), and cultural figures, as well as participatory observation and documentation. The findings reveal that the Wedang ublek tradition is an integral part of the Haul Mbah Abdusshomad Jombor commemoration, conducted annually on the 14th of Dzulhijjah in the Islamic calendar. The tradition involves serving a distinctive beverage called